Quality of Life and Emotional State in Patients with Arterial Hypertension - Palaitytė, Paulė; Mikaliūkštienė, Aldona (Slauga. Mokslas ir praktika, 2022)
An increasing number of patients with arterial hypertension are observed. The symptoms of arterial hypertension harm physical and mental health, causing discomfort that impairs quality of life and disrupts normal and stable life. Studies show that the emotional health of patients is deteriorating as a result of the disease, anxiety and depression are on the rise. The study aimed to analyze the scientific literature on the quality of life and emotional state of patients with arterial hypertension. Research Methods – a Systematic Review of the Literature Articles published in the PubMed, ClinicalKey, Google Scholar, and EBSCO databases on Quality of Life and Emotional State in Patients with Arterial Hypertension. The results show that patients with arterial hypertension are at risk of depression or anxiety disorders, which worsen their emotional state and quality of life.